Predictability of Exchange Rates in Sri Lanka: A Test of the Efficient Market Hypothesis - Guneratne B Wickremasinghe, (Asian Academy of Management Journal of Accounting and Finance, 2007)
This study examined the validity of the weak and semi-strong forms of the efficient market hypothesis (EMH) for the foreign exchange market of Sri Lanka. Monthly exchange rates for four currencies during the floating exchange rate regime were used in the empirical tests. Using a battery of tests, empirical results indicate that the current values of the four exchange rates can be predicted from their past values. Further, the tests of semi-strong form efficiency indicate that exchange rate pairs are significantly correlated at different leads and lags. These results are not consistent with the weak and semi-strong versions of the EMH. The above results have important implications for government policy makers and participants of the foreign exchange market of Sri Lanka.